Model pembelajaran STAD untuk meningkatkan prestasi belajar bahasa indonesia siswa kelas XII IPS-1 - Indriati Suhiroh (Persatuan Guru Republik Indonesia Kota Banjarbaru, 2022)
Until now, the subject of Indonesian is still a compulsory subject at every level of education. Unfortunately, there are many obstacles faced by a teacher to improve student achievement. The STAD (Student Teams Achievements Divisions) learning model is expected to be able to help students overcome this problem. The things discussed in this study are: (a) how is the improvement of Indonesian learning achievement with the implementation of STAD learning in XII IPS 1 class of SMA Negeri 2 Lumajang in the 2022/2023 academic year, (b) how is the effect of learning on STAD on motivation to learn Indonesian in XII IPS 1 class of SMAN 2 Lumajang in the 2022/2023 academic year. This study uses three cycles of action research. Each cycle consists of four stages. The target of this research is the students of XII IPS 1 Class at SMA Negeri 2 Lumajang in the academic year 2022/2023. The data obtained are in the form of competency test results, observation sheets for teaching and learning activities. From the results of the analysis of research results obtained data that student learning achievement has increased from cycle I to cycle III, namely, cycle I (68), cycle II (72), cycle III (78). While the level of student learning mastery in Indonesian subjects also increased, namely cycle I (60%), cycle II (80%), cycle III (92%). The conclusion of this study is that the STAD learning model can have a positive effect on the achievement and learning motivation of students in XII IPS 1 class of SMA Negeri 2 Lumajang in the 2022/2023 academic year, and this learning model can be used to improve the process and learning outcomes of Indonesian.